Thirty Years of Scholarship in the Women and Criminal Justice Journal: Gender, Feminism, and Intersectionality - Posey, Brianne M. (Women & criminal justice, 2020)
Thirty years ago the Women and Criminal Justice (WCJ) journal was founded to provide a venue for the publication of articles by and about women as they interacted with the criminal justice system. A particular focus was given to how patriarchy defined that experience for women caught up in the system as the victimized, accused and convicted, women professionals who worked in the system and women (and men) academics who studied both groups. In our research we reviewed nearly 30 years of articles with special attention to their treatment of gender, feminism, and intersectionality. We found that from the first WCJ was open to the “intersectional” lives of women, and that race, class, and gender influenced the experiences of women as offenders, victims, and practitioners. The analysis of this intersectionality of women’s lives remains a focus of the journal.